Procedimentos rítmico-melódicos na performance de Altamiro Carrilho: um estudo de caso aplicado ao ensino do choro - Marcelo das Dôres Pereira (2016)
This research aimed to study Altamiro Carrilho's rhythmic and melodic procedures that have become performance references for flutists that play choro. Based on my experience as a choro player and as a teacher at the Music School of Universidade do Estado de Minas Gerais (UEMG), this research had the purpose of not only analyzing, but also transcribing and cataloguing these procedures. It also had the objective of investigating how Carrilhos variations, improvisations, ornamentations and other performance practices can be used as teaching and studying tools with students that are interested in this music genre. Carrilhos records of the songs Lamentos, Flor Amorosa, Odeon, Pedacinhos do Céu, André de Sapato Novo and Doce de Coco were selected for this research. They have been transcribed and edited as sheet music in order to be used in the analysis and performances, with special focus on their rhythmic and melodic specific aspects. For one semester, this material was used in an elective subject at the School of Music at the State University of Minas Gerais that was created specifically for this research. During this semester, the students of this discipline had their performances recorded in order to analyze how the contact with Carrilhos performances influenced their interpretation of the songs. We hope that the results of this research may have a relevant contribution for researches about the interpretation of choro.